ADVANCE DIAGNOSTICS TO RESOLVE INTRICATE AND NEGLECTED HEALTH PROBLEMS IN INDONESIA - Teguh Kristian Perdamaian (Berkala Ilmiah Kedokteran Duta Wacana, 2020)
We are proud to present the first full English edition of BIKDW starting from this fifth volume in 2020. In this issue, we present articles on the utilisation of medical technology for daily clinical practice, and research on preventive medicine